Pengaruh Metode Sorogan dalam Pembelajaran Ilmu Tajwid terhadap Kemampuan Membaca Al-Qur’an pada Siswa di SMA N I X Koto Kabupaten Tanah Datar - Ronatio; Januar (Lembaga Yasin AlSys, 2026)
Although the ability to read the Qur’an in accordance with the rules of tajwid is a fundamental competency that students must possess, its implementation in schools continues to face various challenges. The sorogan method has been widely used in Islamic boarding schools, but quantitative studies specifically examining its effect on Qur’an reading ability at the senior secondary school level remain limited. This study aims to analyze the effect of the sorogan method in tajwid instruction on the Qur’an reading ability of Grade X students at SMA Negeri 1 X Koto, Tanah Datar Regency. This study employed a quantitative approach with a quasi-experimental Nonequivalent Control Group Design. The study involved 57 students, comprising 30 students in the experimental class and 27 students in the control class, who were selected through purposive sampling. Data were collected through observation, questionnaires, documentation, and a Qur’an reading ability test. The data were analyzed using descriptive statistics, normality testing, homogeneity testing, and an independent-samples t-test with the assistance of IBM SPSS Statistics version 26. The results showed that the implementation of the sorogan method had a positive and significant effect on students’ Qur’an reading ability, as indicated by a significance value of 0.000 (p < 0.05) and a higher mean posttest score in the experimental class than in the control class. These findings confirm that the sorogan method can be used as an alternative student-centered approach to tajwid instruction to improve Qur’an reading ability. This study contributes to the development of Islamic Religious Education, particularly in selecting effective methods for Qur’an instruction, and may serve as a basis for future research involving broader samples and contexts.